Diffusion-weighted imaging in rectal cancer MRI from theory to practice. - Mayumi Takamune, Debora; Miranda, João; Mariussi, Miriana; Reif de Paula, Thais; Mazaheri, Yousef; Younus, Eyesha; Jethwa, Krishan R.; Knudsen, Cody C.; Bizinoto, Valesca; Cardoso, Daniel; de Arimateia Batista Araujo-Filho, José; Sparapan Marques, Carlos Frederico; et al. (Abdominal Radiology, 2026)
Diffusion-weighted imaging (DWI) has become a cornerstone of high-resolution rectal MRI, providing critical functional information that complements T2-weighted imaging (T2WI) throughout the management of rectal cancer. From baseline staging to restaging after neoadjuvant therapy and longitudinal surveillance during nonoperative management or post-surgical follow-up, DWI improves tumor detection, characterizes treatment response, and facilitates early identification of tumor regrowth or recurrence. This review offers a comprehensive overview of DWI in rectal cancer, emphasizing its technical characteristics, optimal acquisition strategies, and integration with qualitative and quantitative interpretive frameworks. The manuscript also addresses interpretive pitfalls, highlights emerging techniques such as intravoxel incoherent motion (IVIM), diffusion kurtosis imaging (DKI), and small field-of-view DWI, and explores the growing role of radiomics and artificial intelligence in advancing precision imaging. DWI, when rigorously implemented and interpreted, enhances the accuracy, reproducibility, and clinical utility of rectal MRI.